Application of Template Matching on Hand Gestures for Movement Control of a 4-DoF Robotic Arm - Rendyansyah Rendyansyah; Aditya P.P. Prasetyo; Kemahyanto Exaudi; Sarmayanta Sembiring (Jurusan Teknik Elektro Fakultas Teknik Universitas Halu Oleo, 2023)
Humans are very dependent on technology to lighten their work in various fields. One robotics technology that is often applied is in industrial and medical areas. Robotics is a machine that can work automatically or receive instructions from the operator. In general, the application of robots in the industry provides advantages in terms of time and production results. One example of robots in Industry is Robotic Arms, such as medical robots, assembling, welding, picking up and moving objects, and others. In this study, the robot arm has freedom within 4-DoF, and the robot is controlled based on hand gestures using the Template Matching method. The robotic arm navigates based on hand gestures captured by the camera and then processed in the computer. The object used is adjusted to the experimental instrument. The experimental results show that the arm robot 4-DoF can move based on commands from hand gestures with a success rate of 90%.